Treatment of Domestic Wastewater Using Membrane Bioreactor (MBR) Pilot Plant: A Case Study of Wastewater from Kklung Hok’s Treatment Pond and The Environmental Research and Training Centre (ERTC), Pathumthani, Thailand: https://doi.org/10.69692/SUJMRD0901249 - Litthavong, Somvang; Chittima, Charudacha; Mesak, Milintawisamai; Sansanee, Chawanakul (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research performant of Membrane Bioreactor (MBR) pilot plant for treatment of Wastewater from Khlung Hok’s treatment pond volume of 250 liter and The Environmental Research and Training Centre (ERTC) volume of 100 liter, both wastewater was mix on MBR. Aeration was fed at air flow rate 150 l/min over two hours to provide the oxygen for microorganisms. Further, Aeration was fed continuously for 6 hours. sample were collected every one hour. Result found that: the wastewater variation of pH, DO, BOD, COD, NH4+, NO2– concentration of the feed tank from Khlung Hok’s treatment pond were 7.16, 0.60 mg/l, 95mg/l, 157 mg/l, 34.96 ppm and NO2 not found and from ERTC’s wastewater were 6.87, 0.41 mg/l, 93 mg/l, 160 mg/l, 21.23 ppm and 0.043 ppm, respectively. After air flow in MBR over 2 hour the concentration of influent was found 6.64, 0.60 mg/l, 48 mg/l, 105.67 mg/l, 22.30 ppm and 0.031 ppm, respectively. And during the whole process effluent pH concentration were between 6.64-7.46, DO were between 1.11-5.8 mg/l. The removal BOD efficiency were over 89.58% (on 5th hour), COD were over 75.39% (on 4th hour), NH4 were over 53.61% of (on first hour) and were over NO2 48.71% of (on 2nd hour), respectively. Result indicated that effective removal BOD, COD, NH4+ and NO2– by MBR could be achieved and increased in scale for use in the fieldwork or the treatment of wastewater in the environment.